Rancang Bangun Prototipe Buka Tutup Pintu Otomatis Berbasis Arduino Menggunakan Sensor Ultrasonik di Toko Faridh Collection di Desa Ketowan - Septia Nur Imania; Abd. Ghofur; Farihin Lazim (Universitas Islam Raden Rahmat, Malang, 2024)
This research uses qualitative action research method with a focus on developing automatic door prototypes at Faridh Collection Stores. The problems identified were queues and accessibility difficulties at store entrances and exits. As a result, a prototype was successfully built with the integration of Arduino Uno, ultrasonic sensors, buzzers, and servo motors. The prototype is effective in detecting objects near doors and performing automatic movements. It is hoped that this system will ease the flow of customer traffic, improving the convenient shopping experience, especially for customers carrying goods or child strollers. This research shows solutions and hopes on this system to solve queuing problems and accessibility difficulties in Faridh Collection stores